The soybean oil replacement by poultry fat in rations for Nile tilapia fingerlings - Hayashi, Carmino Hayashi; Sanches, Luis Eduardo Ferrari (Pubvet, 2020)
This experiment was carried out with the objective of evaluating the soybean oil replacement by poultry fat for Nile tilapia fingerlings. Two hundred reversed tilapia fingerlings with an individual weight of approximately 0,6 ± 0,11 grams were stocked in 50-liter aquariums, with 8 fishes in each experimental unity, where they were fed with 6,52% lipid rations containing 0, 25, 50, 75, 100 percent of poultry oil replaced by soybean oil as a lipid source in their diets during 50 days. The performance parameters, the carcass composition and the content of fatty acids on both the fillet and the innards were verified. The performance, survival, weight gain and feeding conversion characteristics were not influenced by the diet. The carcass composition was influenced by the lipid source in the moisture content and lipids. In general, the fatty acids profile reflected the diets one with a decrease of polyunsaturated fatty acids and an increase of saturated and monounsaturated fatty acids with the replacement. Therefore, the poultry oil can partially or totally replace the soybean oil in practical diets for Nile tilapia fingerlings without injury to the performance.
Keywords: fatty acids; composition; performance; Oreochromis niloticus; replacement